MENINGKATKAN PEMAHAMAN ARAH MELALUI PERMAINAN “ROLE PLAY” (MAZE) PADA ANAK USIA 5 - 6 TAHUN - Ratna Mandasari; Ajeng Ayu Widiastuti (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Learning while playing is very important for young children aged 5 – 6 years. The game "Role Play" (maze) understanding the direction of the road is carried out "learning by doing" with the child's full direct involvement in the real world. All challenges of difficulty in understanding directions through the implementation of games (mazes) can be overcome in stages in the child's cognitive realm. This is a aspect of ability related to aspects of knowledge, reasoning and thought. This is where the ability to imagine and think intellectually in the cognitive realm will be created. It is possible to observe various very detailed things through the child's visual power in his visual spatial scope. Difficulties that are increasingly complex from understanding directions through games (maze) train children to solve problems by finding solutions to the problems they face. Realized through a sense of enjoyment by playing directly in the real world, through expanding cognitive and visual spatial abilities. The game (maze) of understanding directions that children actually do in the field feels fun and is always done with great joy. Besides that, the game also improves children's development in the form of motor, cognitive, language, emotional and social creativity of children, so that the results obtained, that the game "Role Play" (maze) in children aged 5-6 years can directly improve understanding of directions.). Keywords : Belajar Sambil Bermain, Ranah Kognitif, Kemampuan Visual Spasial